Antecedents of Consumer Preferences for Online Shopping in Jakarta - Rudy Santosa Sudirga (International Journal of Business Studies, 2022)
Research on the antecedents and preferences of consumers shopping online in Jakarta based on the background of the increasing growth of online business in Jakarta. The growth of this online business will have a good impact on improving the economy and also increasing the workforce in Indonesia. This study aims to determine what are the most dominant variables that greatly influence consumer preferences for the success of online businesses in Jakarta. In the long term, it is very useful to know whether these variables can be applied to the success of online businesses in Indonesia. In collecting the necessary research data, the authors took 200 samples of online business buyers in Jakarta as research data. The research data analysis technique is multiple regression analysis. For this causal research, the author will process research data with Structural Equation Modeling.